Introduction to the development of integrated science teaching materials based on inquiry labs to improve students' science literacy - Yusmanila Yusmanila; Zaturrahmi Zaturrahmi (Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study was to describe the science learning process and the teaching materials used by teachers in science learning. The type of research to be conducted is descriptive quantitative research. Respondents in this study were 26 students of class VIIIA MtsN 6 Sijunjung. The research instrument was in the form of a questionnaire filled out by students and an interview sheet with the educator. The result of the research is that the science learning process is more predominantly carried out through the lecture method compared to the experimental / practicum / inquiry labs method by 83% and the teaching materials most often used by teachers in science learning are textbooks by 85%. Science learning has not facilitated students to have scientific literacy because science learning is more often carried out by the lecture method. Thus, teachers need to develop appropriate teaching materials in order to increase students' motivation and scientific literacy.